The effect of ewes synchronization on growth and fattening performances of synthetic ram-lambs - Darcan N.; Ocak S.; Güney O.; Torun O. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The purpose of this study was to evaluate lambing performances of synchronized and natural mated ewes together with the growth and fattening performances of synthetic male lambs, born out of season in the district of Adana in the East Mediterranean Region of Turkey. Growth performances of lambs were observed from birth to weaning time. They were weaned at 2 months of age. After a week, the feedlot period was started. Ten synchronized ram lambs and 10 non-synchronized ram lambs at Cukurova University Research Farm Unit were chosen for evaluation of fattening performance and carcass traits according to birth types and live weights (25 kg) and assigned randomly to two groups. They were group fed. All lambs had ad libitum access to feed and water during the trial. Each morning, lambs were supplied with concentrates and alfalfa hay. After 40 days the feedlot period was completed. Average daily feed intake and daily weight gain for individual lambs were calculated using weekly measurements of body weight and weekly feed intake records. Six lambs in each group were slaughtered. Hot carcass weights, head weights, foot, skin and some visceral organs, fat depots and some body measurements were recorded and dressing percentage was calculated. According to the obtained data, twinning rate was increased almost 37% by hormone treatment. The mortality rate of hormone-treated ewes was found to be higher than non-treated ewes (40%), and lambing rate was higher in the hormone treated group (23%). Daily weight gain and feed efficiency were calculated as 340.1 g and 3.7 kg for hormone treated and 347.3 g and 3.22 kg for non-treated lambs. Dressing percentages were 52% and 54% in hormone treated and non-treated lambs, respectively. The result of this study showed that the crossbred of early ram-lambs can be recommended to produce lamb meat out of season. It can be said that hormone treatment has positive effects on reproduction traits of ewes.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)